Study On The Revenue And Income Of Mungkus Fish Catchers In Padang Guci Hulu District, Kaur Regency - Rita Feni; Anton Feriady; Novitri Kurniati; Jon Yawahar; Elni Mutmainah; Riko Saputra (AGRITEPA: Jurnal Ilmu dan Teknologi Pertanian, 2024)
Purpose: This research aims to determine the amount of revenue and income of mungkus fish finders in Padang Guci Hulu District, Kaur Regency. Method: The research method used in this research is the census method and questionnaires as data collection tools. The respondents in this study were 33 people looking for mungkus fish. Result: The results of the research show that the income of mungkus fish finders in Padang Guci Hulu District is IDR 530,652 per month, with an average income reaching IDR 869,394 per month and an average total cost of IDR 338,742 per month. With an average income of IDR 869,394 per month and an average total cost of IDR 338,742 per month, the income of mungkus fish finders is profitable, This research shows that the subject has not been widely researched and is cost efficient. Findings: This study also highlights a subject that is still under-researched as well as cost-efficient. Novelty: This research provides new insights into the natural resource potential associated with mungkus fish. Originality: This study offers an analysis of the revenue and income of mungkus fish seekers in Kaur Regency. Conclusion: The income earned by mungkus fish seekers is not only profitable, but also serves as an additional source of income to meet family needs. Type of paper : Empirical Research Article